Redes, ideias e ação pública na agricultura urbana: São Paulo, Montreal e Toronto - Oliveira, Lya Cynthia Porto de (2017)
This thesis deals with an analysis of different Urban Agriculture (UA) models of public action. The theoretical model adopted is the cognitive analysis of public action, based on Pierre Muller and Yves Surel, and the actor-network theory by Bruno Latour. The purpose of the thesis is to understand the relationship dynamics between ideas, organizations, networks of action and results in the field of UA public action. The results are understood as basic services for Urban Agriculture, that were defined according to the literature analysis in this field, and it can be offered by state and/or civil society organizations. Based on the literature review of 21 different cities, four different types of public action were identified. These types are formed by the intersection of modes of action of civil society and local government, and they have been termed as 'Marginal', 'Emerging', 'Society-driven', and 'State-driven'. To further understand each type of Urban Agriculture public action, it was carried out a multiple case study with three units of analysis, based on different types of public action. The municipality of São Paulo was selected to further understand the 'Emergent' type, to understand more broadly the 'Society-driven' type, it was selected the City of Montreal and, finally, the municipality of Toronto was chosen to better understand the 'State-driven' type. The research methodology is qualitative and more than 80 semi-structured interviews were carried out, besides document analysis, field visits and participant observation in gardens, political and social meetings of Urban Agriculture. The research demonstrates that, although UA started from different ideas and actions in each municipality, they have become increasingly similar and have mobilized actions in different sectors: community, social, economic and state. The forms of institutionalization of these ideas have also become more homogeneous and tend to be directed to the model of Toronto, where there is greater state support for Urban Agriculture. The results of public action, however, depend on both government actions and civil society. Thus, the municipalities of Montreal and Toronto have good structures for basic services directed to UA. Montreal achieved it due to its strong civil society, and Toronto due to its combination of governmental and non-governmental actions. However, while the city of Montreal needs better planning for this field, Toronto's public management needs to step up some actions to increase food productivity. The city of São Paulo has institutions and civil society under construction, and, although it has increased the structures for basic services directed to Urban Agriculture, it still presents different failures in some specific services.